PRX012 induces microglia‐mediated clearance of pyroglutamate‐modified Aβ in Alzheimer's Disease brain tissue. (31st December 2021) - Tam, Stephen; Zhang, Gang; Li, Lauri; Elmaarouf, Abderrahman; Skov, Michael; Dolan, Philip; Kinney, Gene G; Campbell, Brian; Zago, Wagner M
Abstract: Background: Alzheimer's disease (AD) is a devastating neurodegenerative disorder featuring hallmark Aβ plaques that spread throughout the brain as the disease progresses. Removal of these plaques has been a focal point of research toward developing treatments for AD, and outcomes from multiple development programs support the prediction that monoclonal antibodies (mAbs) that reduce Aβ plaques meaningfully slow clinical decline in AD patients (e.g., aducanumab, donanemab, lecanemab). Donanemab, which specifically targets pyroglutamate‐modified Aβ, was recently reported to reduce Alzheimer's‐related cognitive decline in a phase 2 clinical trial. PRX012 is a high‐potency IgG1 mAb targeting the N‐terminus of Aβ with ∼70pM affinity (KD ) for Aβ fibrils. In the current study, we assessed whether PRX012, an N‐terminal Aβ targeting IgG1 antibody, stimulates microglial‐mediated clearance of Aβ species, including pyroglutamate‐modified Aβ (AβpE3‐42 ), in amyloid plaque‐bearing AD brain tissue. Method: The impact of PRX012, and other Prothena N‐terminal anti‐Aβ antibodies, on microglia‐mediated phagocytic clearance of Aβ plaque species was assessed ex vivo using cryostat sections of human AD brain. Test antibodies or isotype control were applied to plaque‐bearing AD tissue samples, which were then incubated with murine microglia for 72 hours. Determination of total Aβ (Aβ1‐42 ) and AβpE3‐42 levels were assessed by enhanced chemiluminescent detection and ELISA. Result: PRX012 and other Prothena N‐terminal anti‐Aβ antibodies promoted rapid and robust microglia‐mediated clearance of Aβ species associated with plaques in human AD tissue. Compared to isotype control, PRX012 significantly reduced both Aβ1‐42 levels as well as pyroglutamate‐modified Aβ species. Conclusion: PRX012, an N‐terminal‐targeted anti‐Aβ antibody, facilitated abundant microglia‐mediated clearance of Aβ plaque species, including pyroglutamate‐modified Aβ, in brain tissue from AD patients. These data support further development of PRX012 as a potential subcutaneous next‐generation, best‐in‐class Aβ immunotherapy for AD.